Pengembangan Media Audio Visual Berbasis Software Sparkol VideoScribe Pada Pembelajaran Tematik Terpadu di Sekolah Dasarematik Terpadu di Sekolah Dasar - Atika, Fadilatul; Astimar, Nelly (Universitas Negeri Padang, 2024)
The purpose of the study is to determine the validity, practicality, and effectiveness of Sparkol VideoScribe software-based learning media in Theme 7 Thematic Learning at SDN 01 Koto Baru Simalanggang. This type of research is R&D (Research and Development) wearing the ADDIE model of analysis, design, development, implementation, and evaluation. The subjects of this study were 3 trial lecturers, 1 class III teacher and 30 class III students at SDN 01 Koto Baru Simalanggag. The results of the research show (1) audio-visual media based on Sparkol VideoScribe Software in integrated thematic learning in class III was stated to be very valid with the acquisition of media expert scores of 92.5%, material experts 88.2%, and language experts 98%, (2) teacher response The students' fan of the media trials achieved a very practical category with an average teacher response value of 92.5% and student responses of 95.83%, (3) the media was declared effective after the effectiveness test was carried out as seen from the N-Gain value, namely 0,74 with high category